Validating the Crisis, Or the “Technology contra Humanities” argument during COVID-19 through Formal Proofs of Language - Anne Dominique Duque; Fatima Grace Fabillar; Jan Gresil Kahambing (Hasanuddin University, 2021)
The context of the so-called “crisis of the humanities” is further tested against the backdrop of the COVID-9 pandemic crisis. Compounding variations or nuances of this premise infer that the crisis is true, which means that there is a lessening emphasis on the humanities. There is, however, a need to justify how this argument can stand on itself through an inquiry of its validity. The descriptive nature of its claim further begs the presupposition that a crisis is such because of an apparent disparity of the humanities and the sciences stemming from various charges. This paper thus takes over from this problem and utilizes the logical formal proofs of language to assess the underlying assertions being made. It carries on its tasks through a steady establishment of valid proofs that ground the very nature of the crisis.